Velhice e Terceira Idade: tempo, espaço e subjetividade - Rozendo, Adriano da Silva [UNESP]; Justo, José Sterza [UNESP] (My University, 2011)
The elders began to be highlighted in the social scene, not only by their numerical growth, but mainly for their redeployment into new social spaces and accelerating its pace of life. This article aims to analyze the specializations and the time built around the aging and trace its repercussions in the subjectivity production of the oldest. Therefore, it was taken as the object of analysis the differentiation of old age in the aging process.

Os mais velhos passaram a se destacar no cenário social, não apenas pelo seu crescimento numérico, mas, principalmente, pela sua redisposição em novos espaços sociais e pela aceleração do seu ritmo de vida. Este artigo pretende analisar as espacializações e temporalizações criadas em torno do envelhecimento e apontar suas repercussões na produção de subjetividade dos longevos. Para tanto, foi tomado como objeto de análise a diferenciação da terceira idade no processo de envelhecimento.
Aging and Seniors: time, space and subjectivity
Keywords: Old Age; Space; Subjectivity; Velhice; Espaço; Subjetividade